Effects of arsenic on diversity of rice field weeds - Aziz, Abhul; Ahmed, Ashfaque (Dhaka University Journal of Biological Sciences, 2011)
Key words: Arsenic; Rice fields; Weeds; Diversity DOI: http://dx.doi.org/10.3329/dujbs.v19i1.8949 DUJBS 2010; 19(1): 95-98